Review article: the investigation and management of gastric neuroendocrine tumours. Issue 10 (13th March 2014) - Basuroy, R.; Srirajaskanthan, R.; Prachalias, A.; Quaglia, A.; Ramage, J. K.
Summary Background Gastric carcinoids (GCs) or neuroendocrine tumours (NETs) are increasingly identified at endoscopy, and account for 0.6–2% of all gastric polyps identified. The SEER database in the US has demonstrated a rising incidence of gastric NETs amongst all NETs; from 2.2% between 1950 and 1969 to 6.0% between 2000 and 2007. Aim To review the literature and assist clinicians in managing patients with GCs. Methods A literature search was conducted through MEDLINE using search terms: gastric, carcinoid, neuroendocrine tumour, therapy, endoscopy, mucosal resection, submucosal dissection. Relevant articles were identified through manual review. The reference lists of these articles were reviewed to include further appropriate articles. Results There are three types of GCs with important epidemiological, pathophysiological, histological and endoscopic differences that affect prognosis and management. Type 1 and 2 GCs develop in the context of hypergastrinaemia that originates from achlorhydria in atrophic gastritis and a gastrinoma, respectively. Type 3 GCs occur sporadically and independent of gastrin. The histological type, grade and Ki67 index are used to determine prognosis and direct clinical management. Type 1 GCs >1 cm in size and type 2 GCs should be assessed for invasion beyond the submucosa with EUS prior to endoscopic resection with EMR or ESD. Type 3 GCs should be managed as per recommendations for gastric adenocarcinoma. The treatment of advanced disease is multimodal. Conclusions Patients with gastric carcinoids should be discussed in a specialist neuroendocrine tumour multidisciplinary meeting to ensure all treatment options are explored in localised and advanced disease. Areas of controversy exist that need further research.